Is it Necessary to Excise All Breast Lesions? Experience from a University-Based Breast Unit - Ng, Char-Hong (Malays Fam Physician, 2009)
Background: Breast cancer is becoming more important in Asia since it affect the younger age group. Question arises whether it is safe for breast lesions to be left in-situ if all the elements in triple assessment are benign. The aim of this study is to audit all the excision biopsies of breast lumps done in the University Malaya Medical Centre (UMMC), to review the association of age with the type of pathological finding and to evaluate the rate of carcinoma in these biopsies. Methods: We conducted a retrospective study of all women who had excision biopsy of a breast lump in the University Malaya Medical Centre from January 2005 to December 2006. All patients with malignant preoperative biopsies were excluded. Results: Of 717 lesions in 664 patients, 459 (64%) were fibroadenoma, 114 (15.9%) were fibrocystic disease, 20 (2.8%) were phylloides tumour, 27 (3.8%) were papilloma, 59 (8.2%) were malignant and 38 (5.3%) were of other pathology. Of the 717 open biopsies, 449 (62.6%) had fine-needle aspiration cytology (FNAC), 31 (4.3%) had core needle biopsy (CNB), while 14 (2.0%) had both FNAC and CNB done prior to excision biopsy. 251 (35%) had neither FNAC nor CNB. The incidence of fibroadenoma decreased with increasing age and the incidence of fibrocystic changes and papilloma increased with increasing age. There was no association of age with phylloides tumour. The incidence of unexpected malignancy increased with increasing age. The incidence rates were 0.3%, 4.5%, 19.4%, 29.7% and 29.6% for the age group below 30, 30-39, 40-49, 50-59 and above 60 years of age respectively. Of the 59 malignant lesions, FNAC was performed on 47 (79.7%) and CNB on 16 (27.1%). 9 had both FNAC and CNB and 3 had neither FNAC nor CNB. Out of the 56 lesions where FNAC/CNB were done, 23 (41.1%) were reported as benign, 20 (35.7%) as suspicious, 4 (7.1%) as atypical, 5 (8.9%) as inadequate, 2 (3.6%) as equivocal and 2 (3.6%) as lymphoid lesions. Out of the 23 prior biopsies reported as benign, 22 were in the age group above 40. Conclusions: In conclusion, the rate of unexpected malignancy in open biopsies increases with age. It is recommended that all women above the age of 40 presenting with a palpable breast lump or a suspicious non-palpable abnormality on screening mammogram to have their lump excised even though the lump is benign on FNAC or CNB. However, women age of 30 to 39 should also have the lump excised in the presence of other risk factors such as family history of breast cancer.